A control chart for multivariate Poisson distribution using repetitive sampling. Issue 1 (2nd January 2017) - Aslam, Muhammad; Srinivasa Rao, G.; Ahmad, Liaquat; Jun, Chi-Hyuck
ABSTRACT: Control charts using repetitive group sampling have attracted a great deal of attention during the last few years. In the present article, we attempt to develop a control chart for the multivariate Poisson distribution using the repetitive group sampling scheme. In the proposed control chart, the monitoring statistic from the multivariate Poisson distribution has been used for the quick detection of the deteriorated process to avoid losses. The control coefficients have been estimated using the specified in-control average run lengths. The procedure of the proposed control chart has been explained by using the real-world example and a simulated data set. It has been observed that the proposed control chart is an efficient development for the quick detection of the nonrandom change in the manufacturing process.